EFFECTIVENESS OF AL-BARQY METHOD IN IMPROVING THE ABILITY TO READ ARABIC BRAILLE ON STUDENTS IN GRADE 3 AT SDLB PUTRAMANUNGGAL GOMBONG - Budiono Budiono (Universitas Sebelas Maret, 2018)
This study aims to determine the effectiveness of Al-Barqy method to improve the ability to read Arabic braille on students with visual impairments in grade 2 at SDLB Putra Manunggal Gombong, Kebumen. This research is a classroom action research with 3 students of SDLB Putra Manunggal Gombong as the research subjects. This study consisted of 2 cycles that each cycle has 2 times of meetings. The utilized instruments were test sheet, interview sheet, and observation sheet. Triangulation techniques was used to validate the data. The results showed that: 1) the Al-Barqy method was effective in improving students ability to read Arabic braille letters that achieved a good category; 2) the understanding of read Arabic braille of SDLB students was increased through Al-Barqy method. They achieved an average value in the first cycle by number 70,22 with 66,67% learning completeness whereas in the second cycle was 77,56 with 100% learning completeness.